A level-set based multi-material topology optimization method using a reaction diffusion equation. (April 2016) - Cui, Mingtao; Chen, Hongfang; Zhou, Jingling
Abstract: A level-set based multi-material topology optimization method using a reaction diffusion equation is proposed in this paper. Each phase is represented by a combined formulation of different level set functions. This description model is modified from Multi-Material Level Set (MM-LS) topology description model. With a total number of M level set functions, this approach provides a representation of M materials and one void phase (totally M + 1 phases). By this approach, the mathematic model of the multi-material topology optimization problem using a reaction diffusion equation is established. With this model, the geometrical complexity of optimal solutions can be easily controlled by appropriately setting a regularization parameter. Some implementation details for solving this model are also presented in this paper. Finally, several typical numerical examples are shown to confirm the effectiveness of the proposed method. Highlights: A multi-material topology optimization method using a reaction diffusion equation. Modified Multi-material Level Set (MM-LS) topology description model. Controllable geometrical complexity of optimal solutions.